2009
DOI: 10.1136/bmj.b215
|View full text |Cite
|
Sign up to set email alerts
|

Effect of topical alkane vapocoolant spray on pain with intravenous cannulation in patients in emergency departments: randomised double blind placebo controlled trial

Abstract: Objective To assess the efficacy, acceptability, and safety of a topical alkane vapocoolant in reducing pain during intravenous cannulation in adults.Design Randomised double blind placebo controlled trial.Setting Emergency department of a metropolitan teaching hospital.Participants 201 adult patients (54% male), mean (SD) age 58.2 (19.5) years, who required intravenous cannulation.Interventions Less than 15 seconds before cannulation, the skin area was sprayed with either water (control, n=98) or vapocoolant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 17 publications
(33 reference statements)
1
56
0
Order By: Relevance
“…Studies of cannulation following alkane vapocoolant administration also found no significant differences in unexpected events in the vapocoolant groups compared with both lignocaine and placebo administration. 5,7 This study found that alkane vapocoolant spray, when used for local anaesthesia prior to IV cannulation, does not contaminate the sterile cannulation site. It does not appear that bacteria are transmitted from either the spray nozzle or washed from the operator's hand.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Studies of cannulation following alkane vapocoolant administration also found no significant differences in unexpected events in the vapocoolant groups compared with both lignocaine and placebo administration. 5,7 This study found that alkane vapocoolant spray, when used for local anaesthesia prior to IV cannulation, does not contaminate the sterile cannulation site. It does not appear that bacteria are transmitted from either the spray nozzle or washed from the operator's hand.…”
Section: Discussionmentioning
confidence: 95%
“…2e5 Accordingly, less than 20% of medical and surgical doctors use a local anaesthetic agent for the insertion of commonly used cannulae (20 gauge), and less than one-half use a local anaesthetic agent for the insertion of large-bore cannulae. 6 Hijazi et al 5 reported that the administration of a topical alkane spray (vapocoolant), immediately prior to cannulation, reduces the pain of cannulation significantly. Page and Taylor 7 compared vapocoolant spray with subcutaneous lignocaine.…”
Section: Introductionmentioning
confidence: 98%
“…8 Less pain has also been reported with vapocoolant spray use immediately prior to intravenous cannulation and immunisations. 9,10 The purpose of the present study was to assess whether the application of a topical vapocoolant spray immediately prior to the initial intradermal anaesthetic injection at the start of ultrasound-guided breast biopsy decreases pain at the site of the initial injection.…”
Section: Introductionmentioning
confidence: 99%
“…1Y3 Ethyl chloride spray has been used for decades to safely reduce the symptoms of myofascial pain syndromes, 4 and it has also been used in several minor invasive procedures such as intravenous cannulation and vaccination. 5,6 It has been recently found that ethyl chloride spray is more effective than topical anesthetic cream for reducing pain during needle electromyography of the gastrocnemius. 7 However, any effects of cooling on the parameters of the motor unit action potential (MUAP) were not investigated, which might be affected by focal cooling induced by evaporation.…”
mentioning
confidence: 99%